Coaching online : a practical guide - Anthony, Kate; Nagel, DeeAnna Merz (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Translating traditional coaching methods and competencies for use in the online world, this informative and timely guide shows coaches how to transform their face-to-face practice into one that utilizes technological means of communication with clients, mentors, and everyone else associated with their practice. The book offers up-to-the-minute practical and ethical information from two world-expert coaches, leaning on their combined 50 years of experience and study. It covers the practice of online coaching via email, chat, audio/telephone and video methods, as well as the ethics of online coaching (including an ethical framework), case material, supervision, mentoring and training, and a look into the future of the coaching profession in light of technological developments and the culture of cyberspace. Whether you are a coach-in-training or established Coaching Master, this book is an accessible and invaluable tool for taking and maintaining your coaching services online"--
Keywords: Executive coaching; Technological innovations; Web-based instruction; COMPUTERS / Online Services / General; COMPUTERS / Social Aspects / General; PSYCHOLOGY / Psychotherapy / Counseling